Provider experiences with three- and six-month antiretroviral therapy dispensing for stable clients in Zambia. Issue 4 (3rd April 2021) - Phiri, Khumbo; McBride, Kaitlyn; Siwale, Zumbe; Hubbard, Julie; Bardon, Ashley; Moucheraud, Corrina; Haambokoma, Mwiza; Pisa, Pedro T.; Moyo, Crispin; Hoffman, Risa M.
ABSTRACT: Multi-month dispensing of antiretroviral therapy (ART) has been taken to scale in many settings in sub-Saharan Africa with the benefits of improved client satisfaction and decreased client costs. Six-month ART dispensing may further increase these benefits; however, data are lacking. Within a cluster-randomized trial of three- versus six-month dispensing in Malawi and Zambia, we performed a sub-study to explore Zambian provider experiences with multi-month dispensing. We conducted 18 in-depth interviews with clinical officers and nurses dispensing ART as part of INTERVAL in Zambia. Interview questions focused on provider perceptions of client acceptability, views on client sharing and selling of ART, and perceptions on provider workload and clinic efficiency, with a focus on differences between three- and six-month dispensing. Interviews were analyzed using inductive thematic analysis to identify key themes and patterns within the data. Providers perceived significant benefits of multi-month dispensing, with advantages of six-month over three-month dispensing related to a reduced burden on clients, and for reductions in their own workload and clinic congestion. Among nearly all providers, the six-month dispensing strategy was perceived as ideal. Further research is needed to quantify clinical outcomes of six-month dispensing and feasibility of scaling-up this intervention in resource-limited settings. Clinical Trial Number: NCT03101592.